(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Review of the book La Sagesse du Danseur (The Wisdom of the Dancer), by Dominique Dupuy (1930-2024), one of the most emblematic figures of French contemporary dance. The work (originally published in 2011) is a poetic essay in which the author weaves together autobiographical memories of a long-lived artistic career (over 70 years) with profound reflections on dance, on the development of the dancer and on the secrets of teaching this ancient and magical language. To carry out this work, we focused on the Italian version of this work (La Saggezza del Danzatore, 2014), masterfully translated by historian Eugenia Casini Ropa under the watchful eyes of the author.